2023
DOI: 10.3389/fenvs.2023.1107591
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of surface water quality through the use of multivariate statistical techniques: A case study for the watershed of the Yuqiao Reservoir, China

Abstract: In light of the fact that water quality has been threatened by human activities, apportionments of potential pollution sources are essential for water pollution control. Multivariate methods were used to assess the water quality in the Yuqiao Reservoir and its surrounding rivers in northern China to identify potential pollution sources and quantify their apportionment. Fifteen variables at 10 sites were surveyed monthly in 2015–2016. The quality at this location was acceptable according to the water quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Several potentially toxic genera, such as Microcystis, Cylindrospermopsis, Planktotrix, Planktolyngbya, and Anabaena, were dominant throughout our study period (Barros et The ecology of phytoplankton in aquatic environments is affected by seasonal changes, leading to uctuations in species diversity, evenness, the Shannon-Wiener index, and cell density (Sun et al 2023;SureshKumar et al 2019). Temperature is a signi cant factor that regulates the growth of phytoplankton (Somdee et al 2013;Wang et al 2023). During the study, it was observed that species richness decreased in the summer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several potentially toxic genera, such as Microcystis, Cylindrospermopsis, Planktotrix, Planktolyngbya, and Anabaena, were dominant throughout our study period (Barros et The ecology of phytoplankton in aquatic environments is affected by seasonal changes, leading to uctuations in species diversity, evenness, the Shannon-Wiener index, and cell density (Sun et al 2023;SureshKumar et al 2019). Temperature is a signi cant factor that regulates the growth of phytoplankton (Somdee et al 2013;Wang et al 2023). During the study, it was observed that species richness decreased in the summer.…”
Section: Discussionmentioning
confidence: 98%
“…Freshwater dams show variations in physicochemical characteristics based on hydrological cycles and water ow characteristics, which impact the diversity of organisms in freshwater ecosystems, including phytoplankton (Graco-Roza et al 2021). Furthermore, land-based pollution from industrial, agricultural, and urban areas is increasingly being discharged into freshwater reservoirs, resulting in decreased biodiversity in reservoirs (Wang et al 2023). The proliferation of organisms is typically caused by natural events and human activities, including water contamination with nutrients from riverine in ow, leaching, rainfall, aquaculture, and household, industrial, and agricultural activities (Bassem et al 2020;Ponnusamy et al 2023;Sidabutar et al 2020; Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Once again, the multivariate statistical techniques to assess the quality of surface waters are used by Dawood et al [6] by studying the temporal and spatial water quality variability to reveal the characteristics and pollution indicators. Water evaluation via multivariate statistical techniques was also proposed in [7][8][9][10][11][12] followed by study cases that, actually, justify the statistical approaches, and it is sustained using these mathematical approaches.…”
Section: Introductionmentioning
confidence: 99%